1999
DOI: 10.1046/j.1460-9568.1999.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excitotoxic lesions of the rat prefrontal cortex on CREB regulation and presynaptic markers of dopamine and amino acid function in the nucleus accumbens

Abstract: The present study investigated the effects of excitotoxic lesions of the prefrontal cortex (PFC) on dopamine (DA) and excitatory amino acid (EAA) function in the nucleus accumbens core using in vivo microdialysis in freely moving rats. As a postsynaptic marker of neuronal function, the nuclear levels of the transcriptional factor CREB and its active phosphorylated form, CREB-P, were measured in the ventral tegmental area (VTA), and in the core and shell subregions of the nucleus accumbens of sham and lesioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 60 publications
(69 reference statements)
1
25
0
1
Order By: Relevance
“…This is a striking result, replicating the amelioration also found by Passetti and colleagues (2003) but now highlighting the NAC as a likely site of action, based on the findings of Dalley et al (1999) concerning prefrontal cortex-nucleus accumbens interactions. There are several implications of these findings, perhaps the most important being that modulation of dopamine D 2/3 receptors at the level of the NAC significantly blocked the 'impulsive' responding induced by the mPFC lesion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is a striking result, replicating the amelioration also found by Passetti and colleagues (2003) but now highlighting the NAC as a likely site of action, based on the findings of Dalley et al (1999) concerning prefrontal cortex-nucleus accumbens interactions. There are several implications of these findings, perhaps the most important being that modulation of dopamine D 2/3 receptors at the level of the NAC significantly blocked the 'impulsive' responding induced by the mPFC lesion.…”
Section: Discussionsupporting
confidence: 87%
“…(Braun et al 1993;Iversen 1971;Jaskiw et al 1990;Roberts et al 1994;Wilkinson et al 1997). Moreover, previous evidence following similar mPFC lesions had shown that there were enhanced cellular and behavioural responses to d-amphetamine in the nucleus accumbens (NAC) (Dalley et al 1999), suggesting the latter to be the key striatal site mediating the ameliorative effects of sulpiride. Consequently, in this study we directly tested the hypothesis that this amelioration is mediated by dopamine D 2/3 receptors in the NAC by infusing sulpiride there in rats with deficits in 5CSRTT performance produced by mPFC lesions.…”
mentioning
confidence: 93%
“…Previous work has associated CREBactivated transcriptional processes with learning and memory (Bourtchuladze et al, 1994;Liu and Graybiel, 1996;Silva et al, 1998;Dalley et al, 1999;Kogan et al, 2000;Genoux et al, 2002), but the role of such processes in perirhinal-dependent recognition memory has not been investigated. Additionally, previous work implicates CREB-activated pathways in synaptic plasticity (Deisseroth et al, 1996;Silva et al, 1998;Ahn et al, 1999), but their role in perirhinal plasticity is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing both lesioning experiments [13] [14] and pharmacological manipulations [15] [16] have collectively demonstrated the importance of certain structures including the prefrontal cortex (PFC) of the frontal lobe, nucleus accumbens (NAcc), dorsal striatum, hippocampus and amygdaloid nuclei in relation to drug-seeking behaviours and drug-induced plasticity. The frontal cortex has been majorly used for such studies because it contains network of neurons as the substrate for functions that include: comprehension, cognition, communication, reasoning, problem-solving, abstraction, imagination, planning and memory.…”
Section: Introductionmentioning
confidence: 99%